Musik - Politik - Identität Band 3 - Gardner, Matthew; Walsdorf, Hanna (2016)
Music always mirrors and acts as a focal point for social paradigms and discourses surrounding political and national identity. The essays in this volume combine contributions on historical and present-day questions about the relationship between politics and musical creativity. The first part concentrates on musical identity and political reality, discussing ideological values in musical discourses.The second part deals with (musical) constructions, drawing on diverse national connections within our own and foreign identity.